Changes in visual acuity from 4 to 12 years of age in children operated for bilateral congenital cataracts - Magnusson, G (Copyright 2002 British Journal of Ophthalmology, 2002)
Aims: To investigate the long term effects of age at surgery on the development of visual acuity (VA) by measuring VA from preschool age to puberty. Furthermore, to report the VA levels at 12 years of age in a geographically based cohort of operated congenital bilateral cataracts. Methods: All children born in four western counties of Sweden between January 1980 and December 1993 who were diagnosed with congenital cataracts were included in a longitudinal prospective study. The monocular VA of the better eye in 38 subjects was analysed at 4, 7, 10, and 12 years of age, with 20 total and 18 partial cataracts. The mean follow up time was 9.3 years after surgery. Results: The final value of VA was 0.4 or above for approximately 50% of the subjects at 12 years of age. Visual acuity improved to a considerable extent after school age, especially in children who underwent surgery between the ages of 7 weeks and 1 year. Results for partial cataracts were favourable compared to those for total cataracts, reaching a mean of approximately 0.5 at age 12. The mean VA in the group of total congenital cataracts operated on before 7 weeks of age achieved higher values of VA at 4 years of age compared to children with total cataracts operated on between 7 weeks and 1 year of age. However, no statistically significant difference in VA results among these groups could be proved. Conclusion: Visual acuity improves to a considerable extent after school age in children with delayed visual development caused by congenital cataracts. Surgery within 7 weeks results in a more rapid development of VA, initially.